3D printing of spent coffee ground derived biochar reinforced epoxy composites. (October 2021) - Alhelal, Ahmed; Mohammed, Zaheeruddin; Jeelani, Shaik; Rangari, Vijaya K
Semi-crystalline carbon biochar is derived from spent coffee grounds (SCG) by a controlled pyrolysis process at high temperature/pressure conditions. Obtained biochar is characterized using XRD, SEM, and TEM techniques. Biochar particles are in the micrometer range with nanostructured morphologies. The SCG biochar thus produced is used as reinforcement in epoxy resin to 3 D print samples using the direct-write (DW) method with 1 and 3 wt. % loadings. Rheology results show that the addition of biochar makes resin viscous, enabling it to be stable soon after print; however, it could also lead to clogging of resin in printer head. The printed samples are characterized for chemical, thermal and mechanical properties using FTIR, TGA, DMA and flexure tests. Storage modulus improved with 1 wt. % biochar addition up to 27.5% and flexural modulus and strength increased up to 55.55% and 43.30% respectively. However, with higher loading of 3 wt. % both viscoelastic and flexural properties of 3D printed samples drastically reduced thus undermining the feasibility of 3D printing biochar reinforced epoxies at higher loadings.